EFFECTS OF TOTAL QUALITY MANAGEMENT INTEGRATION AND DISCIPLINE ON STUDENT ACHIEVEMENT AT H. NUR ABDULLAH TAHFIDZ - Efnaliza Efnaliza; Adripen Adripen; Dona Afriyani; Akhiyar Hanif; Demina Demina (LPPM UNIVERSITAS BINA INSAN, 2026)
Purpose: This study aims to analyze the effects of integrated Total Quality Management (TQM) and student discipline, both partially and simultaneously, on student achievement at H. Nur Abdullah Tahfiz Al-Qur'an Islamic Boarding School. Research Methodology: This study employed a quantitative approach with a correlational research design at H. Nur Abdullah Tahfiz Al-Qur'an Islamic Boarding School. Data were collected using structured questionnaires measuring integrated TQM, student discipline, and student achievement. The population comprised 134 teachers, dormitory supervisors, and second- and third-grade students. A sample of 100 respondents was selected through probability sampling using a stratified proportional sampling technique. Data were analyzed using simple linear regression and multiple linear regression. Results: The findings revealed that integrated TQM significantly influences student achievement. Student discipline also has a significant positive effect on student achievement. Furthermore, integrated TQM and student discipline simultaneously have a significant effect on student achievement. Conclusions: Student achievement can be improved through the implementation of an integrated Total Quality Management system supported by consistent student discipline within the educational process. Limitations: This study was limited to one Islamic boarding school and included only teachers, dormitory supervisors, and second- and third-grade students. Therefore, the findings may not be generalizable to other educational institutions with different organizational and educational contexts. Contributions: This study contributes to the field of educational management by providing empirical evidence on the role of integrated Total Quality Management (TQM) and student discipline in improving student achievement. The findings may assist school leaders, educators, and policymakers in designing quality management and discipline strategies to enhance educational outcomes, particularly in Islamic boarding schools.